Current Status of Diagnosis and Treatment of High-risk Resistant and Recurrent Gestational Trophoblastic Neoplasia - MAO Mingyi; JIANG Fang; XIANG Yang (Xiehe Yixue Zazhi)
Gestational trophoblastic neoplasia (GTN) patients can be classified into low-risk and high-risk patients based on the International Federation of Gynecology and Obstetrics(FIGO) staging and scoring system. High-risk patients have a higher risk of resistance to single-agent chemotherapy and require combination chemotherapy. Even worse, there are some high-risk patients who develop resistance to combination chemotherapy or experience recurrence after cure. These patients exhibit strong heterogeneity and pose significant challenges to subsequent treatment, thus attracting considerable attention in recent years. Therefore, this article aims to review the risk factors and treatment strategies for high-risk resistant and recurrent GTN patients, in order to provide a basis for early identification of high-risk patients and their precise treatment.